STANDART AKUNTANSI PEMERINTAHAN (SAP) PERATURAN PEMERINTAHAN NO 71 TAHUN 2010 ATAS PERLAKUAN AKUNTANSI-LO DAN BEBAN PADA PEMERINTAH DAERAH - Sari, Indra Mustika; Wahyuni, Nanik (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
AbstractThis Study aimed to analyze the accounting treatment of Revenue-LO and Expenses arising from the change of Government Accounting Standards PP. 24/2015 with Cash Towards Accrual Basis be PP. 71/2010 with Accrual basis. Kediri Regency Government as government entity shall carry out accounting Revenue-LO and Expenses base on accrual-based SAP in accordance with PP. 71/2010 and presented in Statement of Operations (LO) in 2015 with the financial reporting provisions contained in the Statement of Accounting Standards accrual-based government. This research uses descriptive quantitative method is to describe the accounting Revenue-LO and Expenses that occurred in Kediri Regency Government with implementation of the conformity of Government Regulation No. 71/2010 about the Government Accounting Standard so that it can be deduced. The result showed that according to PP. 71/2010, The Government of Kediri Regency had implemented the accrual based accounting for Revenue-LO and Expenses appropriately. The accounting treatment for Revenue-LO dan Expenses which has been analyzed include the recognition, measurement, presentation and disclosure. The Recognition of Revenue-LO and Expenses was made when it arises right and obligations of local government. The measurement of Revenue-LO was carried out with gross principles, while the Expenses measurement was not explained in SAP. The presentation of Revenue-LO and Expenses was presented in the Statements of Operetions (LO) according to the classification in BAS. Disclosure of Revenue-LO and Expenses are disclosed detail in CaLK. Overall, Therefore, it can be concluded that the Kediri Regency Government has done the accounting treatment of Revenue-LO and Expenses in accordance with SAP PP. 71/2010.AbstrakPenelitian ini bertujuan untuk menganalisis perlakuan akuntansi Pendapatan-LO dan Beban yang timbul akibat terjadinya perubahan Standar Akuntansi Pemerintahan PP. 24 Tahun 2005 dengan basis Cash Towards Accrual menjadi PP 71 Tahun 2010 dengan basis Acrrual. Pemerintah Kabupaten Kediri sebagai entitas pemerintah wajib melaksanakan akuntansi Pendapatan-LO dan Beban yang didasarkan pada SAP berbasis akrual sesuai dengan PP. 71 Tahun 2010 dan disajikan dalam Laporan Operasional (LO) pada pelaporan keuangan tahun 2015 dengan ketentuan-ketentuan yang termuat dalam Pernyataan Standar Akuntansi Pemerintahan sehingga bisa ditarik kesimpulan. Hasil penelitian menunjukkan bahwa berdasarkan Peraturan Pemerintah No. 71 Tahun 2010, Pemeerintah Kabupaten Kediri telah menerapkan akuntansi berbasis akrual atas Pendapatan-LO dan Beban secara benar. Perlakuan akuntansi atas Pendapatan-LO dan beban yang telah dilakukan analisis meliputi proses pengakuan, pengukuran, penyajian dan pengungkapan. Pengakuan Pendapatan-LO dan Beban dilakukan ketika timbul hak dan kewajiban Pemerintah Daerah. Pengukuran Pengukuran Pendapatan-LO dilakukan dengan azas bruto, sedangkan pengukuran Beban belum terdapat penjelasan dalam SAP Penyajian Pendapatan-LO dan Beban disajikan dalam Laporan Operasional (LO) sesuai klasifikasi dalam BAS. Pengungkapan Pendapatan-LO dan Beban telah diungkapkan secara rinci dalam CaLK. Dengan demikian secara keseluruhan dapat disimpulkan bahwa Pemerintah Kabupaten Kediri telah melakukan perlakuan akuntansi Pendapatan-LO dan Beban sesuai dengan SAP PP. 71 Tahun 2010.